(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
This study explores the role of musical aesthetics in shaping moral, intellectual, and spiritual development, with a particular focus on Uzbek cultural traditions. Music is presented as more than an artistic form; it is a medium for cultivating empathy, emotional intelligence, and ethical values. Drawing on philosophical perspectives from Aristotle, Kant, and Eastern thinkers, the paper emphasizes music’s capacity to harmonize feelings, stimulate intellectual growth, and foster collective identity. The Uzbek maqom tradition is highlighted as a cultural model where aesthetic beauty, philosophical depth, and moral guidance converge. Contemporary educational philosophy supports the integration of music into curricula as a tool for holistic personality development, combining cognitive, emotional, and cultural dimensions. Ultimately, the aesthetics of music emerge as a universal yet culturally grounded phenomenon, linking beauty, morality, and human creativity.